Kemampuan Komunikasi Matematis Siswa SMA dalam Memecahkan Masalah Matematika Ditinjau dari Tipe Kepribadian MBTI Thinking (T) dan Feeling (F) - Galuh Putri, Yuniar Heksaria; Sa'dijah, Cholis (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study aims to describe the written mathematical communication skills of senior high school students in solving mathematical problems, analyzed through the lens of the Myers-Briggs Type Indicator (MBTI) personality types, specifically the Thinking (T) and Feeling (F) dimensions. Design/methodology/approach: A descriptive qualitative approach was employed in this research. The subjects included 36 eleventh-grade students at a senior high school in Malang. From this group, four students were selected as interview subjects: two representing the Thinking type and two representing the Feeling type. Data collection techniques involved an MBTI questionnaire, a mathematical communication skills test, and in-depth interviews. Findings: The results indicate that students with the Thinking personality type tend to exhibit systematic, logical, and analytical mathematical communication skills across the use of symbols, visual representations, and written solutions. Conversely, students with the Feeling personality type emphasize practicality and emotional aspects in conveying mathematical ideas, while also demonstrating a particular sensitivity to aesthetic presentation. Practical implications: Proficiency in mathematical communication is vital for students to achieve a profound understanding of mathematical concepts. However, PISA 2022 results reveal that the mathematical literacy of Indonesian students requires enhancement, particularly regarding the ability to articulate ideas and solutions clearly and structurally. The Thinking and Feeling MBTI types are deemed highly relevant as they influence how students think, process information, and communicate their understanding during mathematical problem-solving. Originality/value: Initial findings by the researcher suggest distinct patterns in written mathematical communication among students, which are posited to be influenced by their specific personality types.   Purpose: Penelitian ini bertujuan untuk mendeskripsikan kemampuan komunikasi matematis tertulis siswa SMA dalam menyelesaikan masalah matematika ditinjau dari tipe kepribadian MBTI thinking (T) dan feeling (F). Design/methodology/approach: Penelitian ini menggunakan pendekatan kualitatif deskriptif. Subjek penelitian ini adalah 36 siswa kelas XI di salah satu sekolah menengah atas di Kota Malang. Dari subjek tersebut dipilih 4 siswa sebagai subjek wawancara, dengan dua siswa mewakili tipe kepribadian MBTI thinking dan dua siswa mewakili tipe kepribadian MBTI feeling. Teknik pengumpulan data yang digunakan berupa angket MBTI, tes soal kemampuan komunikasi matematis, dan wawancara. Findings: Hasil penelitian menunjukkan bahwa siswa dengan tipe kepribadian MBTI thinking cenderung menunjukkan kemampuan komunikasi matematis yang sistematis, logis, dan analitis, baik dalam penggunaan simbol, representasi visual, maupun penulisan solusi. Sementara itu, siswa dengan tipe kepribadian MBTI feeling lebih menonjolkan kepraktisan dan aspek emosional dalam penyampaian ide matematika, serta menunjukkan sensitivitas terhadap tampilan estetis.Practical implications: Kemampuan komunikasi matematis penting dimiliki siswa untuk memahami konsep matematika secara mendalam. Hasil PISA 2022 menunjukkan hasil literasi matematika siswa Indonesia masih perlu ditingkatkan, terutama kemampuan siswa dalam menyampaikan ide dan solusi secara jelas dan terstruktur. Tipe thinking dan feeling dalam MBTI dinilai relevan karena berpengaruh terhadap cara siswa berpikir, memproses informasi, dan mengomunikasikan pemahaman dalam pemecahan masalah matematika. Originality/value: Temuan awal peneliti menunjukkan adanya perbedaan pola komunikasi matematis tertulis antar siswa, yang diduga dipengaruhi oleh tipe kepribadian.